Litter Production and Nutrient Dynamic on a Moso Bamboo Plantation following an Extreme Disturbance of 2008 Ice Storm - Xiaogai Ge; Benzhi Zhou; Yilin Tang (Advances in Meteorology, 2014)
Ice storm is known to play a role in determining forest succession and litter dynamics constitute an important aspect of nutrient cycling in forest ecosystems. However, ice storm effects on amount and pattern of litterfall are not clearly understood. We investigated litter production and litter leaf nutrient dynamic in a moso bamboo plantation in China following an extreme disturbance of ice storm in 2008. The litterfall in on-years was significantly lower than in off-years. Ice storm caused total litterfall increasing from 16.68% to 35.60% and greatly disturbed the litterfall peak rhythm especially in the on-year. The litter leaf nutrient concentrations at two latitudes significantly fluctuated after ice-snow disaster in 2008, litter leaf stoichiometric traits indicated that litter leaf chemistry showed more easily decomposition with higher C/P ratio, N/P ratio, and lower C/N ratio. It is clear from this study that litterfall restoration dynamic would result in long-term changes in litter nutrient cycling and may help predicting below ground carbon dynamic in future research as well as subtropical forest inventories following extreme disturbance.